Characterization of a novel founder MSH6 mutation causing Lynch syndrome in the French Canadian population. (22nd November 2014) - Castellsagué, E.; Liu, J.; Volenik, A.; Giroux, S.; Gagné, R.; Maranda, B.; Roussel‐Jobin, A.; Latreille, J.; Laframboise, R.; Palma, L.; Kasprzak, L.; Marcus, V.A.; et al.
<x xml:space="preserve">Abstract</x> We identified an MSH6 mutation (c.10C>T, p.Gln4*) causing Lynch syndrome (LS) in 11 French Canadian (FC) families from the Canadian province of Quebec. We aimed to investigate the molecular and clinical implications of this mutation among FC carriers and to assess its putative founder origin. We studied 11 probands and 27 family members. Additionally 6433 newborns, 187 colorectal cancer (CRC) cases, 381 endometrial cancer (EC) cases and 179 additional controls, all of them from Quebec, were used. Found in approximately 1 of 400 newborns, the mutation is one of the most common LS mutations described. We have found that this mutation confers a greater risk for EC than for CRC, both in the 11 studied families and in the unselected cases: EC [odds ratio (OR) = 7.5, p < 0.0001] and CRC (OR = 2.2, p = 0.46). Haplotype analyses showed that the mutation arose in a common ancestor, probably around 430–656 years ago, coinciding with the arrival of the first French settlers. Application of the results of this study could significantly improve the molecular testing and clinical management of LS families in Quebec.